PENGARUH KUALITAS PELAYANAN, PENANGANAN KOMPLAIN, CITRA DAN KEPUASAN TERHADAP BANK BRI UNIT KEBUN BUNGA PALEMBANG - Marina Malian (Institut Informatika Dan Bisnis (IIB) Darmajaya, 2016)
This study aims to determine the effect of service quality, image and satisfaction on customer loyalty. Samples in this study are customers of Bank BRI Palembang Kebun Bunga with a sample size of 80 respondents. The samples in this study using simple random sampling technique. From the data obtained, the analysis of data using multiple regression analysis. The results showed that service quality effect on customer loyalty, and the handling of complaints effect on customer loyalty. Another result of this study indicate that the image and satisfaction jointly effect on customer loyalty.Keywords: Loyalty, Quality of Service, Complaint Handling, Citra, Satisfaction